The Representasi Rekayasa Sosial dalam Film Unlocked (Analisis Semiotika Roland Barthes) - Azwar, Azwar; Auliana, Irvanti (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
This research is about the representation of social engineering in the film "Unlocked" using Roland Barthes' semiotics. This study aims to understand how social engineering is represented in the film "Unlocked." The research employs a descriptive qualitative method. The researcher collected data by analyzing film scenes that exhibit signs of social engineering. Data analysis was conducted using Roland Barthes' semiotic approach, complemented by Stuart Hall's representation theory. The results were drawn through triangulation techniques. The findings of this research indicate that "Unlocked" represents social engineering in the following forms: the denotative meaning of "Unlocked" represents social engineering as a criminal act carried out without a specific motive. The connotative meaning of "Unlocked" represents social engineering as this criminal act is executed through a series of staged patterns, starting from gathering victim information, developing relationships with the victim, exploiting the victim's information, launching an attack on the victim, and requiring professional assistance to complete the process. Victims of this crime are more vulnerable if they have low digital literacy. The mythic meaning in the film "Unlocked" represents social engineering as something that requires a work ethic such as discipline, consistency, and a refusal to back down in achieving its goals.